TLR7 Modulated T Cell Response in the Mesenteric Lymph Node of Schistosoma japonicum-Infected C57BL/6 Mice. (22nd December 2019) - Qu, Jiale; Yu, Xiuxue; Jin, Chenxi; Feng, Yuanfa; Xie, Shihao; Xie, Hongyan; Yang, Quan; Qi, Yanwei; Qiu, Huaina; Chen, Hongyuan; Mu, Jianbing; Zhou, Yi; et al.
Abstract : Toll-like receptors (TLRs) play an important role in regulating immune responses during pathogen infection. However, roles of TLRs on T cells reside in the mesenteric lymph node (MLN) were not be fully elucidated in the course of S. japonicum infection. In this study, T lymphocytes from the mesenteric lymph node (MLN) of S. japonicum -infected mice were isolated and the expression and roles of TLR2, TLR3, TLR4, and TLR7 on both CD4 + and CD8 + T cells were compared. We found that the expression of TLR7 was increased in the MLN cells of S. japonicum -infected mice, particularly in CD4 + and CD8 + T cells (P < 0.05 ). R848, a TLR7 agonist, could enhance the production of IFN- γ from MLN T cells of infected mice (P < 0.05 ), especially in CD8 + T cells (P < 0.01 ). In TLR7 gene knockedout (KO) mice, the S. japonicum infection caused a significant decrease (P < 0.05 ) of the expression of CD25 and CD69, as well as the production of IFN- γ and IL-4 inducted by PMA plus ionomycin on both CD4 + and CD8 + T cells. Furthermore, the decreased level of IFN- γ and IL-4 in the supernatants of SEA- or SWA-stimulated mesenteric lymphocytes was detected (P < 0.05 ). Our results indicated that S. japonicum infection could induce the TLR7 expression on T cells in the MLN of C57BL/6 mice, and TLR7 mediates T cell response in the early phase of infection.